Prenatal thyroid hormones accelerate postnatal growth and telomere shortening in wild great tits - Hsu Bin-Yan; Cossin-Sevrin Nina; Stier Antoine; Ruuskanen Suvi (The Company of Biologists Ltd., 2025)
The early-life environment is known to affect later-life health and disease, which could be mediated by the early-life programming of telomere length, a key hallmark of ageing. According to the fetal programming of telomere biology hypothesis, variation in prenatal exposure to hormones is likely to influence telomere length. Yet, the contribution of key metabolic hormones, i.e. thyroid hormones (THs), has been largely ignored. We recently showed that in contrast to predictions, exposure to elevated prenatal THs increased postnatal telomere length in wild collared flycatchers, but the generality of such effect, the underlying proximate mechanisms and consequences for survival have not been investigated. We therefore conducted a comprehensive study evaluating the impact of THs on potential drivers of telomere dynamics (growth, post-natal THs, mitochondria and oxidative stress), telomere length and medium-term survival using wild great tits as a model system. While prenatal THs did not significantly affect telomere length a week after hatching (i.e. day 7), they influenced postnatal telomere shortening (i.e. shorter telomeres at day 14 and the following winter) but not apparent survival. Circulating THs, mitochondrial density or oxidative stress biomarkers were not significantly influenced, whereas the TH-supplemented group showed accelerated growth, which may explain the observed delayed effect on telomeres. We discuss several alternative hypotheses that may explain the contrast with our previous findings in flycatchers. Given that shorter telomeres in early life tend to be carried until adulthood and are often associated with decreased survival prospects, the effects of prenatal THs on telomeres may have long-lasting effects on senescence.